2021
DOI: 10.1016/j.celrep.2021.109180
|View full text |Cite
|
Sign up to set email alerts
|

Mass-spectrometry-based proteomics reveals mitochondrial supercomplexome plasticity

Abstract: Highlights d Comprehensive quantification of respiratory subunits within supercomplexes d Complexes II and V assemble within supercomplexes d Mitochondrial-encoded subunits display elevated upregulation upon exercise training d Exercise increases ubiquinone biosynthesis enzyme and decreases Lactb complexes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 95 publications
0
35
1
Order By: Relevance
“…We next assessed whether exercise training affects the distribution of ETC complexes into SCs. In contrast to the only previous report showing a post-training redistribution of CIII and CIV (but not CI) into SCs in elderly individuals 15 , and recent research in mouse skeletal muscle showing redistribution of CIV into SCs 54 , our analysis revealed no significant changes throughout the intervention (Fig. 5b , lower panels).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…We next assessed whether exercise training affects the distribution of ETC complexes into SCs. In contrast to the only previous report showing a post-training redistribution of CIII and CIV (but not CI) into SCs in elderly individuals 15 , and recent research in mouse skeletal muscle showing redistribution of CIV into SCs 54 , our analysis revealed no significant changes throughout the intervention (Fig. 5b , lower panels).…”
Section: Resultscontrasting
confidence: 99%
“…2f ; Supplementary Fig. 2d and Supplementary Data 5 ) - an enzyme with an essential role as an electron transfer lipid in OXPHOS processes 59 , which has been shown to be altered following exercise training in mouse skeletal muscle 54 . We identified changes in four constituents (COQ3, COQ5, COQ7, COQ9) of the CoQ synthome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike its prokaryotic homologs, LACTB can polymerize into filaments within the mitochondrial inter-membrane space (Polianskyte et al, 2009). A recent mass spectrometry study demonstrated that endurance exercise training for mouse influences the polymerization degree rather than the total content of LACTB within mitochondria (Gonzalez-Franquesa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…S3A). Furthermore, we have previously detected these adaptations in slow-and fast-twitch muscle fibers following moderate-intensity continuous cycling training (Deshmukh et al, 2021). Given that phosphorylation of myosin light chains promotes myofibrillar calcium sensitivity (Davis et al, 2001), the reduction in both MYLK2 and SMTNL1 alongside an increase in PPP1R12A indicates an adaptation towards reduced myosin phosphorylation and lowered calcium sensitivity following exercise training.…”
Section: Hiit Regulates Proteins Involved In Skeletal Muscle Excitation-contraction Couplingmentioning
confidence: 72%
“…Hostrup, Onslev, Jacobson, Wilson, & Bangsbo, 2018;Majerczak, Karasinski, & Zoladz, 2008;Munkvik et al, 2010;Ortenblad, Lunde, Levin, Andersen, & Pedersen, 2000). Fast-twitch fibers have greater sarcoplasmic reticulum volume, faster calcium release and re-uptake kinetics, and a greater content of DHPR than slow-twitch fibers (Banas, Clow, Jasmin, & Renaud, 2011;Deshmukh et al, 2021;Murgia et al, 2017). Thus, the HIIT-induced reduction of DHPR abundance may represent a slowing of muscle fibers independently of their myosin heavy chain abundance.…”
Section: Hiit Regulates Proteins Involved In Skeletal Muscle Excitation-contraction Couplingmentioning
confidence: 99%